The Philosophical and Social Essence of Corruption and the Stages of its Historical Development - Abdullayev Bobomurod Jorayevich (Scientific Trends, 2025)
This article analyzes the philosophical and social essence of the phenomenon of corruption, its forms of manifestation in social life and the stages of historical formation. The study covers the evolution of corruption from ancient civilizations to modern democratic societies, its impact on social consciousness and its impact on public administration. The article shows the place of normative, ethical and sociological approaches in explaining corruption processes.
Keywords: Corruption, social phenomenon, philosophical analysis, moral crisis, public administration, social development, historical development, sociological approach, principle of justice, social trust, public institutions, spiritual values, bribery, fight against corruption, social consciousness.